Influence of Work Discipline, Work Motivation and Work Competence on the Performance of Central Java Agriculture and Plantation Service Employees - Dewi Ayu Pangukir; Sugiyanta - Sugiyanta; Agus - Suratno (JOBS (Jurnal Of Business Studies), 2022)
Human resources have a very important role to achieve the goals and success of the company. One of them is supported by the behavior of employee who have competent performance. This study aims to test and analyze the influence of work discipline, work motivation, and work motivation on employee performance. The object of research in this paper is employees of the Agriculture and Plantation Service of Central Java Province. The data collection method used a questionnaire that was distributed to 90 respondents using a random sampling technique. The results of this study resulted in findings that partially work discipline variables have a negative and insignificant effect on employee performance, work motivation and work competence have a positive and significant effect on employee performance. Meanwhile, simultaneously the variables of work discipline, work motivation and work competence affect together on employee performance. The value of the coefficient of determination is 0.762 which means that the contribution of independent variables to the dependent variables is 76.2% while the remaining 23.8% is influenced by other variables that were not studied in this study